Toxicity studies of metabolites of some fungal isolates in albino mice. - Pathak, B (1983)
Crude metabolites of 21 of 60 fungal cultures isolated from some of the common cereals collected from different parts of India were found to be toxic. Of these toxin-producing fungi, 79% caused hepatic pathology of varying severity in mice. Serum glutamate pyruvate transaminase values and blood urea nitrogen were found to be high in such experimental animals.